If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13x = 8x + -9 Reorder the terms: 13x = -9 + 8x Solving 13x = -9 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. 13x + -8x = -9 + 8x + -8x Combine like terms: 13x + -8x = 5x 5x = -9 + 8x + -8x Combine like terms: 8x + -8x = 0 5x = -9 + 0 5x = -9 Divide each side by '5'. x = -1.8 Simplifying x = -1.8
| 4(5)-7(4)=-8 | | Z+2=17 | | 3.6(n+5.6)=14.4 | | x+6x=70 | | 4(x-18)=35+3x | | 31x+6=13x-2 | | 31x+6=13x-6 | | -2x+4x=0 | | 258=2x+6x-6 | | Xy+5y=x | | -6(x-2)=-6(x+2) | | 10x+10=15x-5 | | 1+k=-11+5k | | 11x+5=5x+15 | | -44=4z | | (7x+6)+(5x+3)=90 | | 7=3+k | | 74-60x=300 | | -2h=-18 | | 6+5x=-4x+57 | | c=35+0.03 | | ln(2x+6)=7 | | 0.7W+164w=27.28 | | ln(2x+6)=6 | | 8x+2=114 | | s/5=-13 | | -3+13=12x-5-11x | | (2x-3)(2x+3)-4x(x+1)=2(x+3)+3 | | 2q-2=23 | | .35=.50 | | 2m-(x+2)=0 | | log4x=5/2 |